Suppression of metastatic hemangiosarcoma by a parvovirus MVMp vector transducing the IP-10 chemokine into immunocompetent mice - Giese, Nathalia; Raykov, Zahari Zahariev; Dinsart, Christiane; Rommelaere, Jean (Cancer gene therapy, 2002)
We have previously shown that the growth of human tumor xenografts in immunodeficient mice can be efficiently suppressed upon infection with the autonomous parvovirus H-1 or with cytokine-transducing derivatives thereof. To further evaluate the benefits of implementing parvoviruses in cancer gene therapy, we have created a new recombinant vector, MVMp/IP-10, transducing the immunoactive, antiangiogenic chemokine IP-10, and used this virus to treat syngeneic tumors grown in immunocompetent mice. Intratumoral/intraperitoneal administration of only 3×107 replication units of MVMp/IP-10 per animal strongly inhibited the progression of established H5V cell-induced vascular tumors, a highly malignant mouse model for human cavernous hemangioma and Kaposi's sarcoma. Retardation of recurrent tumor growth and suppression of life-threatening metastatic dissemination to internal organs were accompanied by a striking delay in hemangioma-associated mortality. Parental MVMp did not have a significant effect under these conditions up to the dose of 1010 infectious units/animal, but had strong antihemangiosarcoma activity when used to infect H5V cells ex vivo prior to implantation. In all cases, virus therapy was very well tolerated. Virus-induced suppression of hemangiosarcoma was dependent on host T cells and associated with intratumoral persistence of IFNγ-expressing cytotoxic lymphocytes, and led to the reduced expression of hepatic plasminogen activator inhibitor-1 (PAI-1), a metastasis-linked marker. This proof of principle study demonstrates that MVMp/IP-10 can aid the treatment of vascular tumors and that autonomous parvovirus-based vectors can be considered potent tools for cancer gene therapy purposes.
Gesehen am 16.02.2021